Intrinsic photoluminescence of amine-functionalized graphene derivatives for bioimaging applications. (December 2019) - Potsi, Georgia; Bourlinos, Athanasios B.; Mouselimis, Vasilios; Poláková, Kateřina; Chalmpes, Nikolaos; Gournis, Dimitrios; Kalytchuk, Sergii; Tomanec, Ondřej; Błoński, Piotr; Medveď, Miroslav; Lazar, Petr; Otyepka, Michal; et al.
Graphical abstract: Highlights: Photoluminescent graphene derivatives were prepared via fluorographene chemistry. Emission occurs because of the energy gaps engineered by the choice of amine. The hydrophilic amine-functionalized derivative was highly biocompatible. Uptake by cells and localization of graphene-based sheets in cells was shown. The photoluminescent graphene derivatives are applicable in biosensing and bioimaging. Abstract: Photoluminescent graphene-based materials have enormous application potential in cell imaging, display technologies, biomedicine and biosensing. Therefore, their development represents a principal yet highly challenging task for graphene chemistry. Up to now, strategies based on the size confinement in graphene/graphene oxide (GO) quantum dots, non-covalent chemistry combining GO with photoluminescence species, and GO chemistry enabling band gap tuning have been reported. Here, we introduce a simple approach to intrinsically photoluminescent graphene derivatives via one-step fluorographene chemistry enabling controlled surface engineering/chemical reduction by amines. Specifically, the reaction of fluorographene with dodecylamine and hexamethylenediamine results in organophilic and hydrophilic graphene derivatives, respectively, exhibiting intrinsic fluorescence. Both density functional theory calculations and experimental data show that the emission properties occur because of the energy gaps engineered by the choice of amine. Cytotoxicity measurements on NIH/3T3 and HeLa cells demonstrated high biocompatibility for the hydrophilic amine-functionalized derivative. Due to the intrinsic fluorescence, quantification of the uptake by cells and localization of graphene-based sheets in cells can be performed directly using a flow cytometry technique and fluorescence microscopy imaging. These findings pave the way for a new class of functional photoluminescent graphene derivatives with high application potential in fields like biosensing, biomedicine and bioimaging.